A qualitative study of illness narratives: 'overcoming the monster' master plot for patients with stroke. (2nd September 2022) - Alawafi, Rana; Rosewilliam, Sheeba; Soundy, Andrew
Abstract : Background/Aims: Research that considers illness narrative 'master plots' (common and recognisable story plots related to the experience of illness), as expressed by individuals who have had a stroke, is needed Thus far, the literature has focused on identifying pre-established illness narrative master plots: the restitution, the chaos and the quest narrative. However, these narrative plots represent extreme psychological responses to the experience of illness; other narratives need to be understood in order to most effectively support individuals with stroke. Further research must identify if other master plots exist, and consider the implication of such plots. Methods: A narrative methodology was undertaken, contextualised within a social constructivist worldview. A purposive sample of individuals with stroke undertook a single online semi-structured interview. A categorical-form narrative analysis was undertaken in five stages. Results: A total of eight individuals were interviewed. Following analysis, six individuals were identified as illustrating experiences related to a master plot termed 'overcoming the monster'. The 'monster' was represented in several ways, which included: a mental health problem or an expression relating to internal feelings; a sense of being isolated from others; a threat to the individual's independence; and a negative interaction or experience related to health care. Individuals identified clear strategies for 'overcoming the monster'. These included: adopting a different way of viewing life; identifying and attaining both big and small goals; persistence and determination in the face of adversity; and giving support to others through activities and receiving support. Conclusions: Allied health professionals need to understand the importance of this narrativisation of stroke because research has shown that allied health professionals can stereotype interactions by plots and seek to correct them. Implications of these findings ilustate the importance of understanding the individuals experience, not immediately reacting to a narrative type that may seem to fit, understanding the plot of overcoming the monster varies and may need time to be observed.